REALITY, ARTISTIC PERCEPTION, AND THE WRITER’S STYLE OF ERNEST HEMINGWAY - Saidova, Z.X.; Nasimova, F.T (International Conference on Linguistics & Translation, 2026)
This article explores the interrelation between reality, artistic perception, and narrative technique in the works of Ernest Hemingway. It argues that Hemingway’s literary style emerges from a deliberate transformation of lived experience into artistic form through selective representation, symbolic compression, and psychological depth. By examining his aesthetic principles—particularly the “iceberg theory,” minimalism, and objective narration—this study demonstrates how Hemingway redefines reality in fiction. His works reveal that artistic perception is not a passive reflection of life but an active process of structuring meaning through omission, restraint, and implication.